Use of Cone Beam Computed Tomography for Identification of a Distant Causative Tooth: An Unusual Case of an Apical Lesion from a Maxillary Premolar Mimicking That from Maxillary Incisors - Shu Abe; Takashi Muramatsu (Hindawi Limited, 2020)
The article describes an unusual case of an apical lesion at the first premolar with spontaneous pain and swelling around the root and tooth mobility at the maxillary right central and lateral incisors. The patient was a 45-year-old man with a chief complaint of discomfort at the maxillary right central and lateral incisors for one year. Oral examination showed spontaneous pain, swelling, and tooth mobility of the maxillary right central and lateral incisors. Intraoral and panoramic radiographs showed clear apical radiolucency at these sites, although there were no carious incisors. Neither tooth had periodontal pockets, and there was no bleeding on probing sites. A cold thermal examination revealed normal responses of the vital dental pulp. Initial panoramic radiography showed an apical lesion of the maxillary right first premolar, which was root filled and without inflammatory symptoms. A cone beam computed tomography (CBCT) revealed that the apical lesion of the premolar had extensively spread to the anterior through the palatal side, circumventing the palatal side of the adjacent canine, and reached the apical areas of the central and lateral incisors. We treated the apical lesion of the first premolar, and the radiolucent regions had almost disappeared after three years with regard to not only the apical lesion in the first premolar and incisors but also the primary symptoms on the incisors without endodontic treatment. This case shows that CBCT is an effective alternative that allows appropriate treatment to be selected more reliably.